2021
DOI: 10.32598/cjhr.6.3.7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Anxiety, Academic Burnout and Academic Achievement Among Medical Stagers and Interns at Guilan University of Medical Sciences, in 2020

Abstract: Background: Medical students, as part of the healthcare team, are directly exposed to challenging conditions during the COVID-19 epidemic. This study investigated COVID-19 anxiety, burnout, and academic achievement in stagers and interns of Guilan University of Medical Sciences. Materials & Methods: The present analytical cross-sectional study was conducted on medical students and interns studying at Guilan University of Medical Sciences in the 2020-2021 academic year. Of whom, 150 students participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(43 reference statements)
0
6
0
Order By: Relevance
“… Single Medical School Undergraduate 183 Face-to-face VS virtual setting Final exam There is no significant difference in student performance between face-to-face media and virtual settings with the difficulty index of the two exams not much different Darr et al, 33 2021, USA, Cohort. To evaluate the potential impact of the transition to distance learning on examination performance among second-year preclinical medical students at the University of Illinois Peoria School of Medicine (UICOMP) by comparing summative assessment data for medical neuroscience courses over a 2-year period (2019 and 2020), Single Medical School Undergraduate 65 Video conferencing Summative scores There is no difference in the summative value of neuroscience courses between 2019 students and 2020 students Saberi et al, 21 2021, Bahrain, Cross-sectional Study. This study investigated COVID-19 anxiety, burnout, and academic achievement in stagers and interns of Guilan University of Medical Science Single Medical School Undergraduate 138 Corona Disease Anxiety Scale (CDAS) in 2019 to measure the anxiety of COVID- 19 and Maslach Burnout Inventory-Student Survey (MBI-SS) to measure burnout GPA GPA was not significantly correlated with CDAS and MBI-SS H. Yun et al, 22 2021, South Korea, Cross-sectional Study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Single Medical School Undergraduate 183 Face-to-face VS virtual setting Final exam There is no significant difference in student performance between face-to-face media and virtual settings with the difficulty index of the two exams not much different Darr et al, 33 2021, USA, Cohort. To evaluate the potential impact of the transition to distance learning on examination performance among second-year preclinical medical students at the University of Illinois Peoria School of Medicine (UICOMP) by comparing summative assessment data for medical neuroscience courses over a 2-year period (2019 and 2020), Single Medical School Undergraduate 65 Video conferencing Summative scores There is no difference in the summative value of neuroscience courses between 2019 students and 2020 students Saberi et al, 21 2021, Bahrain, Cross-sectional Study. This study investigated COVID-19 anxiety, burnout, and academic achievement in stagers and interns of Guilan University of Medical Science Single Medical School Undergraduate 138 Corona Disease Anxiety Scale (CDAS) in 2019 to measure the anxiety of COVID- 19 and Maslach Burnout Inventory-Student Survey (MBI-SS) to measure burnout GPA GPA was not significantly correlated with CDAS and MBI-SS H. Yun et al, 22 2021, South Korea, Cross-sectional Study.…”
Section: Resultsmentioning
confidence: 99%
“…We divided these factors into internal and external factors. We found nine studies examining students’ internal factors that influence students’ performance such as sleep quality, 23 motivation, 22 anxiety, 19 , 21 stress, 27 , 34 students’ attitude toward online classes, 18 , 25 e-learning style, 18 and level of persistence students. 24 Most studies (n=8) showed a positive and significant correlation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations